Students' Writing Self-Efficacy, Writers' Block, and Academic Writing Performance: An Empirical Study in Eastern Indonesian Students - Lastika Ary Prihandoko (STAI Hubbulwathan Duri, 2021)
This study was conducted to explore the students' perception related to the variables of writing self-efficacy, writers' block, and perceived academic writing performance. The researcher collected data from a University located in Papua Province. This research used an online questionnaire by employing simple random sampling. This study enrolled 280 students as respondents. The researchers used SPSS 23 to conduct a descriptive statistical analysis to determine the proportion of respondents based on the frequency of responses. The findings of this study revealed that the respondents of this study have low perceived levels of writing self-efficacy and academic writing performance. Additionally, students believe they face hurdles that contribute to the issue of writers' block. Further action needs to be taken regarding the findings to enhance the variables related to academic writing performance. The empirical findings from this study can be utilized as the foundation for future research to generate policy to solve issues relating to students' academic writing abilities.